The Existence of Walimatul Urs Traditionally Ibal Serbow Lampung Pepadun Megou Pak Tulang Bawang and Relevance to Islamic Family Law - Antoni, Ferry; Kafrawi, Shalahudin (Universitas Islam Negeri Raden Intan Lampung, 2024)
This article examines the existence of a customary tradition carried out by the indigenous people of Lampung Pepadun Megou Pak Tulang Bawang, this tradition is about Walimatul Urs by Ibal Serbou custom. The purpose of writing is to analyse the view of Islamic law on the implementation of Walimatul Urs in the custom of Ibal Serbou Lampung Pepadun Megou Pak Tulang Bawang, and its relevance to Islamic family law. The method used is qualitative, the type of research is Field Research (field research) supported by Library Research. The approach used is a historical approach, the object of research is carried out in Tulang Bawang Regency, data collection techniques through observation, interviews and documentation. Interview informants were conducted directly to the community and traditional leaders of Lampung Pepadun Megou Pak Tulang Bawang, data analysis techniques inductively with Mashlahah theory. The results of the analysis show that the implementation of Walimatul Urs activities in the customary Ibal Serbou Lampung Pepadun Megou Pak Tulang Bawang involves stages such as Pineng (engagement), pengaku'an (release), and wedding reception. This process requires the participation of the families and communities of the four clans, the Walimatul Urs in the Ibal Serbou custom requires a lot of money and a long time. The implementation of Walimatul Urs in Ibal Serbou custom is not in accordance with Islamic Walimatul Urs activities and is not relevant to Islamic family law.